2018
DOI: 10.1021/acsomega.7b01740
|View full text |Cite
|
Sign up to set email alerts
|

Novel FR-900493 Analogues That Inhibit the Outgrowth of Clostridium difficile Spores

Abstract: The spectrum of antibacterial activity for the nucleoside antibiotic FR-900493 (1) can be extended by chemical modifications. We have generated a small focused library based on the structure of 1 and identified UT-17415 (9), UT-17455 (10), UT-17460 (11), and UT-17465 (12), which exhibit anti-Clostridium difficile growth inhibitory activity. These analogues also inhibit the outgrowth of C. difficile spores at 2× minimum inhibitory concentration. One of these analogues, 11, relative to 1 exhibits over 180-fold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
(125 reference statements)
0
17
0
Order By: Relevance
“…The percentage of hemolysis was calculated from the equation (100 × (A sample −A negative control ) / (A positive control – A negative control )). 41 …”
Section: Methodsmentioning
confidence: 99%
“…The percentage of hemolysis was calculated from the equation (100 × (A sample −A negative control ) / (A positive control – A negative control )). 41 …”
Section: Methodsmentioning
confidence: 99%
“…Although C. difficile spore is naturally resistant to most antibiotics including vancomycin and metronidazole 24,25 , however, in this study, we found that ticagrelor inhibited spore germination in a dose-dependent manner. It has been shown that nucleoside antibiotic derivatives inhibit the outgrowth of C. difficile spores at the concentration of 2X MIC 26 . It is possible that nucleoside analogs may compete with the nucleosides required as germinants for C. difficile spores 27 .…”
Section: Scientific Reports |mentioning
confidence: 99%
“…The monomethoxytetrachlorodiphenylmethoxymethyl (MTPM)-protected uridine 2 was prepared according to the previously reported procedure [1]. The primary alcohol of 2 was oxidized by a modified Swern condition to provide the corresponding aldehyde in quantitative yield, which was then subjected to Carreira’s asymmetric alkynation reaction using (−)- N -methylephedrine [2], yielding the ( S )-propargyl alcohol 3 in 80% yield with selectivity of >98:2. NIS-AgBF 4 promoted ribosylation of ( S )-propargyl alcohol 3 with 4 furnished the β-riboside 5 exclusively in 95% yield.…”
Section: Description Of Protocolmentioning
confidence: 99%